Pengembangan dan Validasi Psikometrik Awal Kuesioner Kebutuhan Bahasa Inggris untuk Praktik Klinis Keperawatan - Christa Vike Lotulung; I Gede Purnawinadi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2026)
There is no validated instrument available to measure the English language needs of nursing students in clinical practice. This study aims to develop and test the validity and reliability of the English Language Needs in Nursing Clinical Practice Questionnaire, developed based on themes from previous qualitative research. This research is a pilot study of instrument development. The questionnaire was tested on 36 nursing students at a private university in North Sulawesi who had undergone clinical practice in a hospital. Construct validity was analyzed using Pearson Product Moment correlation and Corrected Item–Total Correlation, while reliability was tested using Cronbach's Alpha. The questionnaire consisted of 17 questions. All items were declared valid with a calculated r value greater than the table r (0.329) and a Corrected Item–Total Correlation value ranging from 0.345–0.812. The reliability test showed a Cronbach's Alpha value of 0.936, indicating excellent internal consistency. The English Language Needs Questionnaire in Nursing Clinical Practice demonstrated excellent construct validity and reliability during the pilot study. This instrument has the potential to be used to identify the English language needs of nursing students and support the development of English for Nursing Purposes instruction.